Identification of Active Compounds Calotropis gigantea Stem Extracts as Antimalarials Agents on Animal Infected Plasmodium berghei - Shofiyullah, Muhammad; Hayati, Elok Kamilah; Indradmojo, Chrystiaji; Muti'ah, Roâ€™ihatul (Journal of Islamic Pharmacy, 2016)
Thistle (Calotropisgigantea) is a wild plant that contains secondary metabolites as a potential antimalarial drugs.This study aims to determine the content of active compound contained, the potential of ethanol extract of the stem thistle as an antimalarial, and knowing the best eluent used when TLC test.This study covers the extraction of stem thistle using maceration for 24 hours using ethanol 80%.Stirring assisted with shaker for 3 hours. Ekstrak concentrated phytochemical test, antimalarial activity was evaluated by experimental animals mice infected by Plasmodium berghei.Data degree of parasitaemia in mice were analyzed using Minitab 16 with Test TwoWay ANOVA followed by Tukey test.The results showed that ethanol extract stem thistle contains the active compound class of triterpenoids, and potentially as an antimalarial with ED50 values 152.878 mg / kg bw were included in both categories.TLC test results showed that the best eluent for the separation of triterpenoids of stem thistle extract is benzene: chloroform (3: 7) which produced 12 spots with Rf values of 0.04;0.06;0.14;0.21;0.29;0.35;0.41;0.48;0.80;0.84;0.88;0.91.Â Keywords: Antimalarial, Calotropisgigantea, Ethanol 80%, Plasmodium berghei, Thin Layer Chromatography